The historical memory on modernization of the Kazakh aul in Soviet narratives - Saule S. ZhandybayevaАlbina S. Zhanbosinova,; Atantayeva, Bakyt Zh.; Ainur T. Kazbekova, Kuralay R. Zhirindinova, (Opción, 2020)
The study aims to investigate the historical memory on modernization of the Kazakh aul in Soviet narratives via comparative qualitative research of theoretical concepts of modern historical science. As a result, the new Kazakh national identity largely supplanted Kazakhs’ previous identification with a system of pastoral nomadism. In conclusion, the tribal-hierarchical structure did not fit into the Stalinist constitution; the traditional culture of the Kazakh people acquired a new image and a new name for the Soviet-Kazakh ethnos.